The race - Cussler, Clive; Scott, Justin (New York : G.P. Putnam's Sons, 2011)
Bell has never encountered a case- and an enemy- quite like the one before him now, though. It is 1910, the age of flying machines is still in its infancy, and newspaper publisher Preston Whiteway is offering $50,000 for the first daring aviator to cross America in less than fifty days. He is even sponsoring one of the prime candidates- an intrepid aviatrix named Josephine Frost- and that's where Bell, chief investigator for the Van Dorn Detective Agency, comes in. Frost's violent-tempered husband has just killed her lover and tried to kill her, and he is bound to try again. Bell has tangled with Harry Frost before, and knows the man has made his millions leading gangs of thieves, murderers, and thugs in every city across the country. He also knows Frost won't be after just his wife, but after Whiteway as well. And Bell knows that if he takes the case, Frost will be after him, too.--From front book jacket.
Keywords: Bell, Isaac (Fictitious character) -- Fiction; Private investigators -- Fiction; Suspense fiction